MANGA MATRIX: SEBUAH PENDEKATAN DALAM PERANCANGAN VISUALISASI KARAKTER PADA PROJECT INTEGRATED INTERNATIONAL EXHIBITION INDONESIA-JAPAN SEBAGAI PERWUJUDAN STANDAR IDENTITAS MASKOT - Handaru, Wuri Cahya (Narada : Jurnal Desain dan Seni, 2025)
This research focuses on developing visual identity through a mascot as an effective strategy to support the branding of international events. The study centers around the design of SWEN, the mascot for the Brawijaya International Design Exhibition (BIDEA) at Malang Creative Center (MCC), which represents the values of innovation, creativity, and cross-cultural collaboration between Indonesia and Japan. The development of this mascot applies the Manga Matrix theory framework by Hiroyoshi Tsukamoto, integrating character design elements such as Form Matrix, Costume Matrix, and Personality Matrix. Additionally, a design thinking approach was used to ensure the design centered on user needs through the stages of empathize, define, ideate, prototype, and test. The first stage, empathize, involved interviews with manga artists and character designers to explore the cultural values to be depicted. The second stage, define, focused on clearly articulating the problem based on the insights gathered. The third stage, ideate, generated initial ideas and design concepts. In the fourth stage, a visual prototype of the mascot was developed for implementation in the exhibition. The fifth stage, test, involved conducting a questionnaire survey among exhibition visitors, designers, and manga enthusiasts to gather feedback. During the three-day BIDEA exhibition at MCC, the study engaged participants through a Likert scale 4-based questionnaire to evaluate the mascot's success. The analysis revealed that over 80% of respondents agreed that the SWEN mascot effectively became a relevant and functional visual identity for the international exhibition. The results of the design were applied in both offline and online media during the Indonesia-Japan international event. The study concludes that combining the Manga Matrix theory and the design thinking approach produced a mascot design that is not only visually appealing but also carries strong representational values. This study contributes to the development of character design for international event branding and reinforces the role of mascots as a tool for cross-cultural communication.